Welfare: Theoretical and analytical paradigms - Susanne MacGregor (United Nations Research Institute for Social Development (UNRISD), 2014)
The paper reviews paradigms of welfare, principally the industrialization thesis, the three worlds of welfare and social investment states and shows how these link to wider public policies and underlying assumptions. It locates explanations in historical and contemporary contexts. The literature of social policy is seen to be both descriptive and prescriptive and to have developed in response to key crises. The paper considers arguments for and against universalism and targeting, and shows how these concepts fit within theories of welfare. It considers lessons from this review for discussions of how to develop social security and health systems in emerging economies and indicates the value of systems that include all or the vast majority of the population, organized around principles of collective social insurance and recognize the value of caring work. Proposals have, however, to be set in economic systems with fair, living wages and progressive income tax structures goals which run counter to the current trajectory of financial capitalism.
Keywords: 330